Bio-Electrical Properties of Body Tissues in Obese Women after a Program Composed by Physical Exercises and Nutrition Education. (2016) - Melo, Camila Maria de; Louzada, Eliana Regina; Kehayias, Joseph J; Tirapegui, Julio; Ribeiro, Sandra Maria Lima
No abstract available